Dynamic analysis and comparison of single-phase induction motor with a switching and double capacitors - Sünter, Sedat; Özdemir, Mehmet; Gümüş, Bilal (My University, 2002)
In order to get maximum torque in the single-phase induction motor one of the methods is to use a switching capacitor in the auxiliary winding. This configuration with an electronic switch connected across the capacitor makes possible to obtain a maximum torque by using a single capacitor. Optimal capacitor values are used to obtain the maximum torque and to improve the performance of a single-phase induction motor at steady-state and transient operations. These variable capacitor values are obtained by controlling the duty cycle of the electronic switch. In this paper the dynamic model for the single-phase induction motor with the switching capacitor has been obtained by using MATLAB/Simulink software package program. Simulation results are presented to verify the high performance operation of the single-phase induction motor at transient and steady state.
Dinami?ka analiza i usporedivanje jednofaznog indukcijskog motora s preklopnim i dvostrukim kondenzatorima
Keywords: Dynamic modelling; Single-phase induction motor; Switching capacitor